Electronic structure and magneto-optical Kerr effect in the compound UCuP2: Магнетизм - Horpynyuk, O.; Nemoshkalenko, V. V.; Antonov*, V. N.; Harmon, B. N.; Yaresko, A. N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The optical and magneto-optical (MO) spectra of the ternary compound UCuP2 are investigatedfrom first principles, using the fully relativistic Dirac linear-muffin-tin-orbitalband structure method and density-functional theory in the local spin-density approximation. Within a band-like description of the 5f electrons, good agreement with the measured MOspectra is obtained. The origin of the Kerr rotation in the compound is examined.